In vitro antifungal effect of a plant-based product, CIN-102, on antifungal resistant filamentous fungi and their biofilms. Issue 9 (7th September 2021) - D'agostino, Maurine; Tesse, Nicolas; Lavergne, Rose Anne; Le Pape, Patrice; Frippiat, Jean Pol; Machouart, Marie; Debourgogne, Anne
Abstract : Introduction. The increase of invasive fungal infections (IFIs) and associated treatment failure in populations at risk is driving us to look for new treatments. Hypothesis. The CIN-102 compound, derived from cinnamon essential oil, could be a new antifungal class with an activity, in particular, on strains resistant to current antifungals but also on biofilms, a factor of virulence and resistance of fungi. Aim. The aim of this study is to show the activity of CIN-102 on various strains resistant to current antifungals, on the biofilm and to determine the possibility of resistance induced with this compound. Methodology. We studied the MIC of CIN-102 and of current antifungals (voriconazole and amphotericin B) using CLSI techniques against eight different strains of three genera of filamentous fungi involved in IFIs and having resistance phenotypes to current antifungals. We also determined their effects on biofilm formation, and the induced resistance by voriconazole (VRC) and CIN-102. Results. MIC values determined for CIN-102 were between 62.5 and 250 µg ml −1 . We demonstrated the antifungal effect of CIN-102 on biofilm, and more particularly on its formation, with 100 % inhibition achieved for most of the strains. CIN-102 at a sub-inhibitory concentration in the medium did not induce resistance in our strains, even after 30 generations. Conclusions. In this study we show that CIN-102 is effective against resistant filamentous fungi and against biofilm formation. In addition, our strains did not acquire a resistance phenotype against CIN-102 over time, unlike with VRC. CIN-102 is therefore an interesting candidate for the treatment of IFIs, including in cases of therapeutic failure linked to resistance, although further studies on its efficacy, safety and mechanism of action are needed.